MRI IMAGE CLASSIFICATION FOR DETECTING BRAIN TUMOR USING DEEP NEURAL NETWORK (International Journal of Food and Nutritional Sciences, 2019)
Brain tumor identification is really challenging task in early stages of life. But now, it becameadvanced with various machine learning and deep learning algorithms. Nowadays, braintumor automatic identification is of great interest. To detect the brain tumor, the MRI imagesof patient’s are used.